Pembelajaran Berdasarkan Kesiapan Teknologi Dan Sarana Prasarana Dalam Peningkatan Pendidikan Sekolah - Achmad Asyaari (Journal of Innovation in Teaching and Instructional Media, 2025)
This study examines the influence of technological readiness and facilities in schools on the quality of the teaching and learning process. In today’s digital era, educational technology is very important to create a comfortable learning atmosphere and can be adjusted to students’ needs. But in reality, the readiness of each school to use technology and its supporting facilities is quite diverse. The study used a descriptive method, collecting data through documents from several articles. The results show that schools that are ready with technology, such as digital devices and good internet connections, usually make the learning process more enthusiastic, efficient, and more focused on students. In addition, physical facilities such as adequate classrooms, projectors, and laboratories for practice also have an influence on learning success. Another important factor is the teacher’s ability to incorporate technology into learning and support from school management to plan technology-based learning materials. So, the quality of learning is not only about teaching methods, but is also influenced by the readiness of technological infrastructure and other facilities. The suggestion from this study is that schools should be given more support to improve technological facilities and infrastructure so that the learning process becomes more relevant and of high quality in this digital era.